Pemodelan Enterprise Arsitektur Sistem Informasi Penjualan Obat Menggunakan Kerangka TOGAF ADM - Umi Faddillah; Nurfia Oktaviani Syamsiah; Indah Purwandani (Indonesian Journal on Software Engineering (IJSE), 2019)
Abstract: Enterprise information system architecture has covered various fields, one of which is the pharmaceutical industry which has also changed significantly. Pharmaceutical companies and all business lines around the world are forced to reconsider their business priorities and strategies to deal with uncertainty, volatility and complexity. Where it will be handled in the presence of an integrated system. In this research the implementation of information system technology is carried out by implementing the TOGAF ADM framework that will help companies in architectural modeling starting from designing system architecture, business process architecture, drug sales information system architecture, technology architecture, several proposed architectural designs for business opportunities, and proposals system changes running. The result is that the enterprise modeling information system sales architecture to produce architectural blueprints can be done in six stages in the TOGAF ADM framework. Keywords: TOGAF, Sales, Pharmaceutical